CURRENT TRENDS IN THE DEVELOPMENT OF THE MARKET OF TOURIST SERVICES OF UKRAINE IN MODERN CONDITIONS - MOISIEIEVA, NATALIIA; KRUPITSA, IRYNA; BAIRACHNA, OKSANA (Herald of Khmelnytskyi National University. Economic sciences, 2021)
The article establishes that in the current conditions of economic development of Ukraine tourism is one of the most promising industries. There is a positive trend in the provision of tourist services, which indicates that the number of foreign tourists visiting the country has decreased, while sharply increased outbound tourism. In addition, research shows a serious dissatisfaction with domestic demand for tourism products. It is established that in order to meet the demand for the tourist product in the country and abroad, Ukraine has proposed certain areas of development of tourist services. We can say about the introduction of new methods of tourism, improvement of traditional forms of tourism, full use of the tourist potential of tourist destinations. From the economic and social point of view the direction of development of the industry of tourist services of the country in modern conditions is perspective. The paper highlights the current situation and current issues of industry development, as well as possible areas of development of tourist services. Tourism can help increase revenues at all levels of the budget, increase employment opportunities and attract domestic and foreign investment. At the same time, the modern development of the tourism industry of Ukraine is characterized by deep contradictions in its organizational structure, direction of development, qualitative and quantitative characteristics.